Mapping the Plasticity of Morphology, Molecular Properties and Function in Mouse Primary Microglia - Jiang, Xue; He, Hui; Mo, Li; Liu, Qin; Yang, Fan; Zhou, Ying; Li, Liangyuan; Su, Dapeng; Yi, Saini; Zhang, Jinqiang (Frontiers in Cellular Neuroscience, 2022)
Microglia exert diverse functions by responding in diverse ways to different stimuli, yet little is known about the plasticity of various phenotypes that microglia display. We used interferon (IFN)-γ, interleukin (IL)-4 and IL-10 to induce different phenotypes in mouse primary microglia. RNA sequencing was used to identify genes differentially expressed in response to stimulation, and the different stimulated populations were compared in terms of morphology, proliferative capacity, phagocytic ability and neurotoxicity. IFN-γ induced an “immunodefensive” phenotype characterizing both induction of filopodia and upregulation of inducible nitric oxide synthase and tumor necrosis factor α. Microglia with this phenotype mediated an acute inflammatory response accompanied by excellent proliferative capacity and neurotoxicity, and remained susceptible to remodeling for up to 48 h after initial stimulation. IL-4 induced an enduring “neuroimmunoregulatory” phenotype involving induction of lamellipodium and persistent upregulation of arginase (Arg)-1 and YM-1 expression. Microglia with this phenotype remained susceptible to remodeling for up to 24 h after initial stimulation. IL-10 induced an “immunosuppressive” phenotype involving induction of amoeba-like morphology and upregulation of transforming growth factor  and IL-10 as well as inhibition of inflammation. This phenotype was accompanied by inhibition of self-proliferation, while its morphology, molecular properties and function were the least susceptible to remodeling. IFN-γ, IL-4 or IL-10 appear to induce substantially different phenotypes in microglia. The immunodefensive microglia induced by IFN-γ showed remarkable plasticity, which may help repair CNS inflammation damage under pathological condition. Chronic activation with IL-10 decreases microglial plasticity, which may help protect the brain form the immune response. Our research justifies and guides further studies into the molecular pathways that operate in each phenotype to help multitasking microglia regulate homeostasis in the brain.